Aplikasi Modifikasi Algoritma Vigenere Cipher dan Hill Cipher Menggunakan Konversi Suhu - Aurillya Queency; Sisilia Sylviani (Mathematical Sciences and Applications Journal, 2023)
Cryptography is a method used to maintain the confidentiality of messages and data. Modifications or combinations of algorithms can be made to make the process of cracking secret messages more difficult than just one algorithm. This research aims to apply a combination of modified Vigenere Cipher algorithm, modified Hill Cipher algorithm, and temperature conversion equations to maintain a message’s confidentiality. By determining one plaintext and the required keys, the encryption and decryption process uses a modified Vigenere Cipher algorithm, a modified Hill Cipher algorithm, and all temperature conversion equations. The results obtained in the encryption process of one plaintext are 12 different ciphertexts according to the temperature conversion equation used. Moreover, the results obtained in the decryption process of 12 different ciphertexts are the original plaintext.